The Stockholder – A Lesson for Business Ethics from Bioethics? - Hardwig, John (Journal of business ethics, 2010)
Business ethics – both stockholder and stakeholder theories – makes the same mistake as the one made by the traditional ethics of medicine. The traditional ethics of medicine was a teleological ethics predicated on the assumption that the goal of medicine was to prolong life and promote better health. But, as bioethicists have made plain, these are not the only or even the overriding goals of most patients. Most of us have goals and values that limit our desire for medical treatments. Similarly, the view of the stockholder in business ethics is that the stockholder has only one interest – profit. If stockholders have no other values or interests that would limit their desire for additional profit, their sole interest is in profit maximization. But investors are real people with interests and values that balance and limit their desire for profit. It would be an extremely odd individual who cared for nothing except more profit. And institutional investors are supposed to serve the interests of individual investors. Stockholders hold many stakes in the firms in which they invest. The conclusion that most stockholders have interests that would limit the pursuit of maximum profit has significant implications both for business ethics and for the management of for-profit corporations. Something like “informed consent for investors” is needed. Corporate managers, to the extent that they are to be agents of their stockholders, must not simply pursue profit maximization. They must ascertain the interests and values of their investors that limit the single-minded pursuit of profit.